2023
DOI: 10.3390/su152014694
|View full text |Cite
|
Sign up to set email alerts
|

A Sustainable and Environmentally Friendly Concrete for Structural Applications

Kabiraj Phuyal,
Ujwal Sharma,
James Mahar
et al.

Abstract: The purpose of this study is to utilize waste products—precipitated calcium carbonate (PCC) and upcycled recycled concrete aggregate (upcycled RCA or UCA)—in civil works projects. To do so, tests must be performed to determine the engineering properties of the materials in which PCC and UCA are sequestered. PCC is a fine to coarse grain waste product generated during the production of sugar from sugar beets. UCA is produced from demolished and returned concrete by the extraction of primarily calcium and alkali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It was challenging for the ISU team to ascertain whether PCC had a binding effect on concrete. Thus, this study serves as supporting research for the concrete research mentioned in [26,27]. [26,27].…”
Section: Precipitated Calcium Carbonate (Pcc)mentioning
confidence: 66%
See 2 more Smart Citations
“…It was challenging for the ISU team to ascertain whether PCC had a binding effect on concrete. Thus, this study serves as supporting research for the concrete research mentioned in [26,27]. [26,27].…”
Section: Precipitated Calcium Carbonate (Pcc)mentioning
confidence: 66%
“…The research on concrete conducted by our team found that Portland cement can be replaced by PCC up to 30% by weight while still maintaining the compressive strength of concrete above 27.6 MPa (4000 psi) [26,27]. However, there is a decreasing trend in compressive strength as the amount of PCC content increases, as shown in Figure 1.…”
Section: Precipitated Calcium Carbonate (Pcc)mentioning
confidence: 99%
See 1 more Smart Citation